Tobacco Cessation Practices and Perceived Barriers for its Implementation among Nepali Dentists - Khapung, Anju; Vaidya, Samriddhi (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
Introduction: Tobacco use and its resulting ill health effects can be controlled by adopting appropriate cessation measures at individual, community and national level. Health care service providers, and particularly dentists, can play a major role in providing tobacco cessation counselling to the patients who come in their contact. Objective: To assess the tobacco cessation practices and perceived barriers for its implementation among Nepali dentists. Methods: This descriptive cross-sectional study using online questionnaire for data collection was done among 246 Nepali dentists selected by convenient sampling from November, 2020 to January, 2021 after ethical clearance from institutional review committee of Nepal Medical College. Data entered into Google Forms were exported to Microsoft Excel and SPSS v.20 for descriptive analysis. Results: A total of 246 (111, 45.1% male and 135, 54.9% female) dentists responded to the survey. Mean age of the respondents was 30.75±4.61 years. Most respondents (159, 64.6%) were from Bagmati province. Out of the participants, 204 (82.9%) were “never smokers” themselves. Most of the participants (161, 65.5%) asked patients about smoking habits, 176 (71.6%) advised patients not to start smoking and 119 (48.4%) rarely advised quitting tobacco. Only 15 (6.1%) dentists assisted patients to quit smoking. Among the perceived barriers, most reported lack of trainings (143, 58.1%). Conclusion: Even though majority of the study participants asked their patients about smoking habits, only few assisted them to quit. Those having received trainings regarding tobacco cessation being fewer in number further suggests the need of regular continuing medical education and trainings.